Most Sacred direction of the Kazakh literary art (about the Kazakh literature in China). (Eurasian Journal of Philology Science and Education, 2015)
The article deals with the process of research and development of Kazakh literature abroad, as an important part of modern Kazakh literature. We give a description of the features and manifestations of literary and culturalachievements of Kazakhs abroad. Taken under the guidance of a number of works of researchers who work for the benefit of Kazakh literature. Studied scholarly works that examine the direction of artistic and aesthetic development and thematic and ideological foundations of Kazakh literature in China. Including in article analyzed the works of such poets as Akyt Ulimzhiuly, Tanzharyk Zholdyuly who left an indelible mark in the Kazakh literature, describes some of the moments of life and creativity Kazhygumara Shabdanuly who wrote a six-volume novel "Kylmys" also founded the Kazakh literature in China. Marked peculiarity of Kazakh literature abroad, which is making its share in the artistic development of the current Kazakh literature.
Keywords: Kazakh nation; Kazakh diaspora; Kazakh literature in abroad; Kazakh literature in Shynzhan; Akyt Ulimzhiuly; Tanzharyk Zholdyuly; Kazhygumar Shabdanuly